2018
DOI: 10.1038/s41598-018-21596-3
|View full text |Cite
|
Sign up to set email alerts
|

A role for tau in learning, memory and synaptic plasticity

Abstract: Tau plays a pivotal role in the pathogenesis of neurodegenerative disorders: mutations in the gene encoding for tau (MAPT) are linked to Fronto-temporal Dementia (FTD) and hyper-phosphorylated aggregates of tau forming neurofibrillary tangles (NFTs) that constitute a pathological hallmark of Alzheimer disease (AD) and FTD. Accordingly, tau is a favored therapeutic target for the treatment of these diseases. Given the criticality of tau to dementia’s pathogenesis and therapy, it is important to understand the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 65 publications
1
78
1
1
Order By: Relevance
“…The mechanisms underlying the increase in anxiety-like behavior following tau ablation in mice are unknown and may involve several mechanisms. Conversely, other studies did not detect an anxiogenic phenotype in 6 or 7-months-old TauKO mice in the zero maze (29) and open field (26) behavior tests. These differences in results might be due to the age, strain and sex of the animals, as well as behavior test protocol used in each study.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The mechanisms underlying the increase in anxiety-like behavior following tau ablation in mice are unknown and may involve several mechanisms. Conversely, other studies did not detect an anxiogenic phenotype in 6 or 7-months-old TauKO mice in the zero maze (29) and open field (26) behavior tests. These differences in results might be due to the age, strain and sex of the animals, as well as behavior test protocol used in each study.…”
Section: Discussionmentioning
confidence: 85%
“…Our group and others have shown that tau ablation triggers glucose intolerance, brain insulin resistance and pancreatic dysfunction in mice, suggesting a physiological role for tau protein in metabolic regulation (20,21). The effects of tau ablation in mood-related behavior remains to be better elucidated and thus far, inconsistent results have been generated (22)(23)(24)(25)(26)(27)(28)(29). Here, we complement our previous metabolic findings on TauKO mouse by investigating the impact of tau loss of function on systemic insulin sensitivity, anxiety-related behavior and memory.…”
Section: Introductionmentioning
confidence: 99%
“…The overproduction of cytotoxic molecules and proinflammatory cytokines by brain-resident immune cells, such as microglia, launches signaling pathways in neurons, consequently inducing brain tissue damage [142]. Numerous studies have pointed out that overexpression of IL-1β aggravates AD pathogenesis, owing to tau hyperphosphorylation [143], which inhibits long-term potentiation and affects synaptic plasticity [144,145]. Furthermore, IL-1β inhibition in a mouse model has yielded disease-modifying improvements in the pathology of AD [146].…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…Af ew studies have shown that some engineered strains of cutinases (i.e., Thermobifida fusca and F. solani pisi)a nd an esterase from Clostridium botulinum have better PET and Nylon 66 hydrolytic performances by changing their superficial hydrophobicity. [21,22,291] However,t hese strains have not been used for the reversereaction (i.e.,esterification).…”
Section: Next Step Of Development:e Nzyme Mutagenesismentioning
confidence: 99%